ANALISIS PENGARUH RETURN ON ASSET, DEBT TO EQUITY RATIO, DIVIDEND PAYOUT RATIO, DAN SIZE TERHADAP PRICE TO BOOK VALUE (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN PERIODE 2018 – 2022) - Dandono, Yustinus Rawi; Aprilia, Dina (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
The aim of this research is to analyze the influence of Return On Assets (ROA), DebtTo Equity Ratio (DER), Dividend Payout ratio (DPR) and SIZE on Price to Book Value(PBV) in banking companies listed on the Indonesia Stock Exchange (BEI ) for theperiod 2018 – 2022. The data source used is secondary data with the researchsample determined using purposive sampling. The number of samples used in thisresearch was 4 companies from a population of 20 banking companies. The methodused in this research is multiple linear regression involving classical assumptiontests, followed by partial significance using hypothesis testing, namely the t test,while to find out simultaneously, the f test uses a significance level of 5%. Theresearch results show that partially the DPR variable has no effect on Price to BookValue (PBV). Meanwhile, the variables ROA, DER and SIZE have a significant effecton Price to Book Value (PBV). Meanwhile, simultaneously the variables ROA, DER,DPR, and SIZE influence PBV. The adjusted R-squared value in this study was 0.974.This shows that 97.4% of Price To Book Value (PBV) is influenced by Return OnAssets (ROA), Debt To Equity Ratio (DER), Dividend Payout ratio (DPR) and SIZEwhile the remaining 2.6% is explained by independent variables others such asEarning Per Share (EPS), Net Profit Margin (NPM), Return On Equity (ROE),Inflation Rate, Interest Rate, and others.